Characterization of Pain After Inside-Out Transobturator Midurethral Sling - Cadish, Lauren A. (Female Pelvic Med Reconstr Surg, 2014)
OBJECTIVES: This study aimed to evaluate the prevalence, severity, duration, and location of pain after transobturator midurethral sling. METHODS: We evaluated patients who underwent inside-out transobturator sling from March 2011 through February 2013. Presence of pelvic girdle pain, its severity, and location were documented preoperatively and at 2- and 6-week postoperative visits. Pain severity was measured on a scale of 1 to 10, with 10 being the “worst imaginable” pain. RESULTS: Of the 130 women analyzed, the median age was 50.0 years (interquartile range, 44.0–62.0). Thirty-nine percent of women reported preoperative pain, mostly mild with a median score of 1.0 (1.0–5.0). The most common sites of postoperative-onset pain were the lateral leg, medial leg, groin, and low back. Women reporting preoperative pain were not more likely to report postoperative-onset pain than women without preoperative pain (P = 0.42). Twelve percent of women at 2 weeks and 0.8% at 6 weeks reported severe postoperative-onset pain. Women reporting postoperative-onset pain were equally likely to be satisfied with the procedure as those without pain at 2 (P = 0.76) and 6 (P = 0.74) weeks. CONCLUSIONS: Women undergoing transobturator sling commonly report preoperative pain. An expected postoperative increase in pain generally resolved by the sixth postoperative week. The lateral leg was the most common site of pain. Postoperative-onset pain was not associated with decreased patient satisfaction.